Mergers and acquisitions and environmental conditions: a systematic literature review to investigate their linkage - Battisti, Enrico; Nirino, Niccolò; Leonidou, Erasmia; Thrassou, Alkis; Vrontis, Demetris (My University, 2024)
Purpose: The purpose of this paper is to systematically examine and organize the literature that has explored the effects of several environmental conditions (ECs) on mergers and acquisitions (M&As), in particular highlighting the increasing role of protectionism. Design/methodology/approach: The systematic literature review methodology was applied for the purpose of identifying, analyzing and interrelating specific ECs that affect M&As, thereby underlining and elucidating the requisite role of protectionism. Specifically, this research is based on 51 methodically selected peer-reviewed articles published from 1991 to 2020. Findings: The research summarizes and assesses the current state of relevant literature through comprehensive and coherent descriptive and thematic analysis. The proposed conceptual framework allows us to recognize the connections between M&As and external conditions, highlighting varying degrees of study and in-depth analysis across the different areas under consideration. Originality/value: This study contributes to original and significant knowledge, by developing a conceptual framework that descriptively classifies existing knowledge; by defining refining and explicating the theoretical foundations for scholars to build on; by identifying the research gaps and proposing effective avenues for impactful further research; and by presenting practitioners and policymakers with a practical guide to implementation.
Keywords: Systematic literature review; Mergers and acquisitions